THE STRATEGIES OF PROMOTION STRATEGIES AND THE ROLE OF ENGLISH FOR EARNING HOTEL PROFIT - Vinka Beby Salsabila; Andi Anto Patak; Fatimah Hidayahni Amin; Muhammad Fahri Jaya Sudding (International Journal of Business English and Communication, 2025)
This study looks at promotion strategies and how using English increases revenue for the Mercure Hotel Makassar. Effective promotion strategies and fluent English usage are essential for drawing both domestic and foreign guests in the hospitality industry. Open-ended and structured interview questions were used to gather data from guests and hotel managers. The study's findings indicate that the Mercure Makassar Hotel uses four different promotional strategies: differentiation, market segmentation, target market, and market position. Every strategy has a set of tasks. The study's findings also indicate that English serves three purposes: first, it is a language associated with formality and upper class; second, it is a language that staff members use to communicate with foreign visitors; and third, it is an international language that is used in international communication. The research study's findings support the notion that hotel management can plan and target promotional strategies to help them achieve their primary objective of increasing hotel profits